2012
DOI: 10.2175/106143012x13373550426670
|View full text |Cite
|
Sign up to set email alerts
|

Modeling External Carbon Addition in Biological Nutrient Removal Processes with an Extension of the International Water Association Activated Sludge Model

Abstract: BSTRACT: The aim of this study was to expand the International Water Association Activated Sludge Model No. 2d (ASM2d) to account for a newly defined readiiy biodegradable substrate that can be consumed by polyphosphate-accumulating organisms (PAOs) under anoxic and aerobic conditions, but not under anaerobic conditions. The model change was to add a new substrate component and process terms for its use by PAOs and other heterotrophic bacteria under anoxic and aerobic conditions. The Gdansk (Poland) wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…In this study not only biological part of WWTP was simulated but more complex newly developed model of whole plant Mantis2 (which is extension of well known ASM) was calibrated/validated, behaviors of real date NH 4 -N and NO 3 -N and PO 4 -P in the anoxic/aerobic tank of full-scale MUCT bioreactor, as a sample results presented Figure 2c, were matched accurately by the model predictions in the GPS-x simulator. Moreover full-scale simulations during the validation process revealed that addition of winter scenario in Mantis2 compensate with the temperature parameters resulting in a similar NH 4 -N and NO 3 -N and PO 4 -P behavior compared to the reference case (data not shown) presented earlier by Swinarski et al [3].…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…In this study not only biological part of WWTP was simulated but more complex newly developed model of whole plant Mantis2 (which is extension of well known ASM) was calibrated/validated, behaviors of real date NH 4 -N and NO 3 -N and PO 4 -P in the anoxic/aerobic tank of full-scale MUCT bioreactor, as a sample results presented Figure 2c, were matched accurately by the model predictions in the GPS-x simulator. Moreover full-scale simulations during the validation process revealed that addition of winter scenario in Mantis2 compensate with the temperature parameters resulting in a similar NH 4 -N and NO 3 -N and PO 4 -P behavior compared to the reference case (data not shown) presented earlier by Swinarski et al [3].…”
Section: Resultssupporting
confidence: 62%
“…The process calibration in newly developed comprehensive model Mantis2 for simulation study of "virtual" plant layout with the full-scale MUCT bioreactors in GPS-x were started with calibrated results of a series of batch tests with the process biomass (ASM2d) in order to match accurately kinetic/stoichiometric parameters. Then previous model of "Wschód" WWTP [3] as a basepoint of further process calibration was used in conjunction with optimization techniques Nelder-Mead simplex to estimate kinetic/stoichiometric parameters in Mantis2 as was shown in Table 3. The simulations run on the calibrated and validated plant-wide Mantis2 model included scenarios that may influence the WWTP process operation and energy balance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies focused specifically on modelling the effects of external carbon addition on PAOs with the ASMs so far. Swinarski et al (2012) developed a new model as an expansion of ASM2d to predict the effect of adding a readily biodegradable substrate to a combined N/P system. The aim of this study was to further modify the ASM2d with regard to the behaviour of PAOs under aerobic conditions in the presence of external carbon (acetate).…”
Section: Introductionmentioning
confidence: 99%